Melanesian mainstream : stringband music and identity in Vanuatu - Ellerich, Sebastian T., 4 0 16; 5 (New York : Berghahn, 2024)
Citizens of Vanuatu (ni-Vanuatu) perceive stringband music as a marker of national identity, an indicator of their cultural, stylistic, and musical heritage. Through extensive field and ethnographic research, Melanesian Mainstream offers a detailed historical record of the roots, context, evolution, and impact of stringband music. Beyond chronicling the genre's history and cultural significance, this thorough monograph positions the genre's musical hybridity, communal lyrics, and unique organizational structures as key factors in the anthropological understanding of ni-Vanuatu socio-cultural history-- Provided by publisher.
Introduction -- A History of Stringban Miusik in Vanuatu -- Stringban Miusik and Its Musical Characteristics -- Lyrics -- The Music Industry in Vanuatu -- Stringbands as Social Groups -- Conclusion. Vanuatu Stringban Miusik and Other Musics in Oceania.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; History and criticism.;History and criticism.;Social aspects -- String band music; Folk music;Music;String bands -- Vanuatu; Vanuatu;Vanuatu.;Vanuatu.; 20; 2